2008
DOI: 10.1128/mcb.01088-07
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Gene That Coordinates Epigenetic Controls and Transcriptional Interference To Achieve Tissue-Specific Expression

Abstract: The mouse fpgs gene uses two distantly placed promoters to produce functionally distinct isozymes in a tissue-specific pattern. We queried how the P1 and P2 promoters were differentially controlled. DNA methylation of the CpG-sparse P1 promoter occurred only in tissues not initiating transcription at this site. The P2 promoter, which was embedded in a CpG island, appeared open to transcription in all tissues by several criteria, including lack of DNA methylation, yet was used only in dividing tissues. The patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 69 publications
(68 reference statements)
2
17
0
Order By: Relevance
“…It has been suggested that silencing of an alternative promoter of the mouse fpgs pc gene is an example of transcription inducing silencing without introducing chromatin changes [82], but this system has not been subject to a similar genetic analysis and alternative explanations remain possible. How RNAPII from an interfering promoter is able to suppress functional transcription of the overlapped promoter remains to be determined, but stalling of the interfering RNAPII elongating over the sensitive promoter has been suggested to block access of essential TFs [30,83].…”
Section: Transcriptional Interference In the Absence Of Chromatin Chamentioning
confidence: 99%
“…It has been suggested that silencing of an alternative promoter of the mouse fpgs pc gene is an example of transcription inducing silencing without introducing chromatin changes [82], but this system has not been subject to a similar genetic analysis and alternative explanations remain possible. How RNAPII from an interfering promoter is able to suppress functional transcription of the overlapped promoter remains to be determined, but stalling of the interfering RNAPII elongating over the sensitive promoter has been suggested to block access of essential TFs [30,83].…”
Section: Transcriptional Interference In the Absence Of Chromatin Chamentioning
confidence: 99%
“…Indeed, in eukaryotes from yeast to mouse, transcription through promoter regions is known to disrupt transcription start sites and suppress gene expression (reviewed in refs. [27][28][29]. In these cases the production of the small RNA is functionally important, but the small RNA itself may not be.…”
Section: The Function and Evolution Of Tirnasmentioning
confidence: 99%
“…Richard Moran studied the epigenetic control of tissue-specific expression for FPGS. He examined the contrast between the promoters in liver and kidney, and the promoters in proliferating tissues and tumor that utilized IRES and are unmethylated (56). …”
Section: Session V: Therapeutic Targets and Novel Strategies In Gastrmentioning
confidence: 99%